2003
DOI: 10.1128/jvi.77.2.943-952.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Multimerization of Hantavirus Nucleocapsid Protein Depends on Type-Specific Epitopes

Abstract: Multimerization of the Hantaan virus nucleocapsid protein (NP) in Hantaan virus-infected Vero E6 cells was observed in a competitive enzyme-linked immunosorbent assay (ELISA). Recombinant and truncated NPs ofHantaviruses, which are classified in the family Bunyaviridae, genus Hantavirus, are the causative agents of two rodent-borne viral zoonoses: hemorrhagic fever with renal syndrome (HFRS) and hantavirus pulmonary syndrome (HPS) (22,30). Each hantavirus appears to have a single predominant rodent species tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
35
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 38 publications
10
35
0
Order By: Relevance
“…One can conclude either that the residue alone is crucial or that the mutation disrupts the folding of the C-terminal region and destroys the interaction. Interestingly, W119 of Seoul virus N protein was shown to have a similar effect on N protein interaction in the yeast two-hybrid system (34). These data suggest that the tryptophan helps to maintain the overall structure of the N protein.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…One can conclude either that the residue alone is crucial or that the mutation disrupts the folding of the C-terminal region and destroys the interaction. Interestingly, W119 of Seoul virus N protein was shown to have a similar effect on N protein interaction in the yeast two-hybrid system (34). These data suggest that the tryptophan helps to maintain the overall structure of the N protein.…”
Section: Discussionmentioning
confidence: 60%
“…Previously published data suggest the N-terminal region as one of the candidates: (i) the N-terminal regions of Tula virus N protein (residues 1 to 43) and Sin Nombre virus N proteins (residues 1 to 39) were shown to participate in the homotypic interaction in the two-hybrid assays (1,10), (ii) the N-terminal residues of hantavirus N proteins were predicted to form coiled coils (1), and (iii) oligomerization studies of N protein peptides corresponding to residues 3 to 75 assembled into trimeric coiled coils (2). Other regions, e.g., the one that includes amino acid residues 100 to 125, may also be essential for the interaction (34). As soon as the C-terminal regions of three N protein monomers are brought closer to each other, this will allow helix II-helix I contact (as described in this paper), which occurs in a cyclic manner between neighboring N protein molecules, completing trimer formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a study by Alfadhli et al, the C-terminal regions of the Sin Nombre virus and Prospect Hill virus N proteins were required for N protein-N protein interactions in a yeast two-hybrid assay (2). Furthermore, in a recent study by Yoshimatsu et al, HTNV, Seoul virus, and Dobrava virus N protein multimerization was observed in a competitive enzyme-linked immunosorbent assay even when 49 amino acids were deleted from the N-terminal region (38). Additionally, using a yeast two-hybrid assay, they found that amino acids 100 to 125 and 404 to 429 were required for N protein multimerization.…”
Section: Discussionmentioning
confidence: 99%
“…The cDNAs that contain the coding sequences for the HTNV GPs G1 and G 2 and the NP were subcloned into the expression plasmid pCAGGS/MCS (15) and designated pCHTNM (16) and pCHTNS (27), respectively. Vero E6 cell monolayers at 80% confluency were prepared in eightchamber LabTek Chamber Slides (Nunc, Inc., Naperville, Ill.) 1 day before transfection.…”
Section: Cells and Virusmentioning
confidence: 99%